ROLE DE L’ENVIRONNEMENT HOSPITALIER DANS LA PREVENTION DES INFECTIONS NOSOCOMIALES: SURVEILLANCE DE LA FLORE DES SURFACES A L’HOPITAL EL IDRISSI DE KENITRA - MAROC - Saouide el ayne Nabila; Echchelh Adil; Chaouch Abedelaziz; Auajjar Nabila; Hamama Samir; Soulaymani Abdelmajid (European Scientific Journal, ESJ, 2014)
The fight against nosocomial infections particularly those related to the germs of the hospital environment is part of the priorities of health care facilities. Thus, the control of contamination of hospital surfaces is realized through microbiological controls, these controls are subject to rules set by recommendations of experts and normative texts. Periodic controls, primarily microbiological ones, must be implemented in order to spot any contamination, determine a microbial ecology of the hospital and carry out preventive actions, corrective actions, procedures, protocols, and make a fundamental approach aiming at the control of infectious hazards in the hospital system. The objective of our study is to determine the microbial ecology of the hospital, Region Rharb, EL IDRISSI – Kenitra – Morocco, so as to reduce the rate of nosocomial infections. To this end, we performed 210 samples in total, 15 of which were negative. The overall distribution of germs by service showed their predominance in the units of intensive care (28%), traumatology (11%), emergency (10%) and operating room (8%). The most frequently isolated germs: Bacillus (27%) and Staphylococcus negative coagulases (26%) were predominant, followed by Staphylococcus aureus (20%) and Klebsiela pneumoniae (16%). Finally Pseudomonas aeruginosa in proportion of 5% as well as Enterobacter cloacae of 5% and Proteus vulgaris of 1%.